Объяснение:
г) (6x + 2y)/y + (6x -3y)/y = (6x + 2y + 6x -3y)/y = (12x - y)/y
д) (x + y)/3a - (3x - y)/3a = (x + y - 3x + y)/3a = (2y - 2x)/3a = (2(x -y))/3a
6х + 2у ║ 6х - 3у ║ 12х - у
+ =
у ║ у ║ у
х + у ║ 3х - у ║ 2х + 2у
- =
3а ║ 3а ║ 3а
║ ставлю на случай если пробелов не будет ( чтобы отделить дроби)
Объяснение:
г) (6x + 2y)/y + (6x -3y)/y = (6x + 2y + 6x -3y)/y = (12x - y)/y
д) (x + y)/3a - (3x - y)/3a = (x + y - 3x + y)/3a = (2y - 2x)/3a = (2(x -y))/3a
6х + 2у ║ 6х - 3у ║ 12х - у
+ =
у ║ у ║ у
х + у ║ 3х - у ║ 2х + 2у
- =
3а ║ 3а ║ 3а
║ ставлю на случай если пробелов не будет ( чтобы отделить дроби)